The Effect of Institutional Pressure on the Level of BPK Auditor Reliance: A Study of Government Audit Institutions in Indonesia - R. Usman; R. Masdar; . Masruddin (Финансы: теория и практика)
Supreme Audit Agency (BPK) and Government Internal Supervisory Apparatus (APIP), as government audit institutions, have an essential role in realizing the accountability of state financial management. Both are expected to establish good coordination because it can benefit both the audit institution and the government organization being audited. This study examines the effect of institutional pressure, namely coercive pressure, normative pressure and mimetic pressure, on the level of BPK auditor reliability. In addition, this study also aims to examine the impact of BPK auditor reliability on audit quality. The research was conducted at government audit institutions considering that reliability is a form of coordination in conducting government financial report audits. The survey method was carried out to collect data from 264 audit team leaders tasked with examining the government’s 2020 financial reports. SEM PLS analysis was used with the help of the WarpPLS Version 8 software. Unlike previous studies, this study found that mimetic pressure does not affect the level of auditor reliability. BPK is the only external government audit institution so no other audit institutions can be used as a benchmark in auditing government financial reports. The study also concluded that BPK auditors’ reliance on APIP could improve audit quality. This research provides input for the government regarding strategies to improve coordination and cooperation between BPK as the government’s external auditor and APIP as the government’s internal auditor.